Detection of Bacteroides fragilis Enterotoxin Gene by PCR - Shetab, Razeq (American Society for Microbiology, 1998)
Bacteroides fragilis constitutes about 1% of the bacterial flora in intestines of normal humans. Enterotoxigenic strains of B. fragilis have been associated with diarrheal diseases in humans and animals. The enterotoxin produced by these isolates induces fluid changes in ligated intestinal loops and an in vitro cytotoxic response in HT-29 cells. We developed a nested PCR to detect the enterotoxin gene of B. fragilis in stool specimens. After DNA extraction, a 367-bp fragment was amplified with two outer primers. The amplicon from this reaction was subjected to a second round of amplification with a set of internal primers. With these inner primers, a 290-bp DNA fragment was obtained which was confirmed as part of the B. fragilis enterotoxin gene by Southern blotting with a nonradioactive internal probe and a chemiluminescence system. By this approach, B. fragilis enterotoxin gene sequences were detected in eight known enterotoxigenic human isolates and nine enterotoxigenic horse isolates. No amplification products were obtained from DNA extracted from 28 nonenterotoxigenic B. fragilis isolates or B. distasonis, B. thetaiotaomicron, B. uniformis, B. ovatus, Escherichia coli, or Clostridium difficile. The sensitivity of this assay allowed us to detect as little as 1 pg of enterotoxin DNA sequences or 100 to 1,000 cells of enterotoxigenic B. fragilis/g of stool. Enterotoxin production of all isolates was confirmed in vitro in HT-29 cells. A 100% correlation was obtained between enterotoxin detection by cytotoxin assay and the nested PCR assay. This rapid and sensitive assay can be used to identify enterotoxigenic B. fragilis and may be used clinically to determine the role of B. fragilis in diarrheal diseases.